2018
DOI: 10.1111/jse.12418
|View full text |Cite
|
Sign up to set email alerts
|

Try Tri again? Resolving species boundaries in theLomatium triternatum(Apiaceae) complex

Abstract: Species boundaries have traditionally been delimited by applying phenotypic characters to a morphological species concept. With an increased understanding of the complexities of speciation as a process, species concepts have proliferated while at the same time, the ability to gather greater numbers and types of molecular characters has expanded the means by which species can be delimited. Phylogenetic studies of molecular data provide an opportunity to identify reciprocally monophyletic groupsand have led to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…In the current study, we recovered clades that agree with described species (Lomatium packardiae) or geographic regions (Figs. 2, 3) that were not recovered in any prior molecular analysis (George et al, 2014;Smith et al, 2018a) or identifiable with keys based on morphological data (Hitchcock and Cronquist, 1973;Cronquist et al, 1997). Previous studies using Sanger-based sequencing that…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, we recovered clades that agree with described species (Lomatium packardiae) or geographic regions (Figs. 2, 3) that were not recovered in any prior molecular analysis (George et al, 2014;Smith et al, 2018a) or identifiable with keys based on morphological data (Hitchcock and Cronquist, 1973;Cronquist et al, 1997). Previous studies using Sanger-based sequencing that…”
Section: Discussionmentioning
confidence: 99%
“…The four southern subclades are also part of a polytomy; however morphologically and geographically, L. packardiae and the East-Central Oregon populations are more similar, and likewise, the Mann Creek and Hell's Canyon populations are more similar. In an earlier study, Smith et al (2018a, see their fig. 3) found that according to leaflet morphology, L. packardiae and the Mann Creek/Hell's Canyon separated into two forms, Form A and Form B, respectively.…”
Section: Species Boundariesmentioning
confidence: 93%
See 2 more Smart Citations
“…Until now, the majority of plant species have been delimited by taxonomists based on morphological analyses of character variation (morphological species concept, MSC) (Lewin, 1981;Henderson, 2005;Smith & al., 2018). However, this approach to species delimitation presents many shortcomings either due to intra-specific morphological variation or little morphological difference between closely related species (Pratt & Clark, 2001;Whittall & al., 2004).…”
Section: ■ Introductionmentioning
confidence: 99%